RISK FACTORS IN THE DEVELOPMENT OF CONGENITAL HEART DEFECTS - Togaev M.K (Лучшие интеллектуальные исследования, 2023)
Was studied perinatal risk factors in 80 infants with congenital heart disease, where poor obstetric history revealed the mother in the I-st trimester, physical illness mother and dysfunctional family. Было изучено перинатальные факторы риска у 80 детей раннего возраста с врожденными пороками сердца, где выявлено плохой акушерский анамнез у матери в I-м триместере, соматические заболевания матери и неблагополучная семья.